Au@bovine serum albumin nanoparticle-based acid-resistant nanozyme quartz crystal microbalance sensing of urine glucose. Issue 46 (17th October 2022) - Zhou, Dengfeng; Song, Wenyao; Zhang, Shuangbin; Chen, Lan; Ge, Guanglu
Abstract : Tandem nanozyme (Au@BSA NPs) QCM sensor fabricated by one-step deposition method can be used to detect non-enzymatic urine glucose based on precipitation-amplified signal. Abstract : A robust, efficient and sensitive quartz crystal microbalance (QCM) for glucose detection has been constructed using Au@bovine serum albumin (Au@BSA) nanoparticles as an active layer. The nanoparticles serve as tandem nanozymes and their stability over natural enzymes enable the sensor to show a wider linear dynamic range between 0.05 and 15 mM, a higher acid-resistance (pH 2.0–8.0) and heat-resistance (35–60 °C) than conventional glucose oxidase (GOx)-based sensors. The sensor has been further applied to measure glucose content in artificial urine directly without dilution, where the recovery of 99.6–105.2% and the relative standard deviations (RSDs) below 0.88% confirm a good reproducibility for the measurement results. In addition, the developed Au@BSA QCM sensor can retain 95% of its initial activity after 40 days of storage. Overall, the Au@BSA sensor shows better comprehensive performance than the commercial sensor strips for urine glucose analysis and provides a promising approach in a more precise and robust manner.